নির্বাচিত বেগম : অর্ধশতাব্দীর সমাজচিত্র, ১৯৪৭-২০০০, তৃতীয় খণ্ড - বেগম, মালেকা.; আনিসুজ্জামান. (ঢাকা : পাঠক সমাবেশ, 2006)
Contributed articles on socioeconomic conditions of women in Bangladesh and erstwhile East Bengal; selections from various issues published between 1947 and 2000 of 'Begama' journal on women's issues published from Bangladesh.
AAL
Bokhari Boi Ghar
In Bengali.
Keywords: Women -- Bangladesh -- Social conditions; Women -- Bangladesh -- Economic conditions; Women's periodicals